Religious Motivation and Consumer Boycotts: Enhancing Global Peace and Moral Justice: Enhancing Global Peace and Moral Justice - Arinta, Yusvita Nena; Mutmainah, Siti (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
Boycotts become a global campaign with orders not to buy certain products from one or all companies in a country. Boycotting a product brand is still voluntary, religious factors are the main driving force in carrying out a boycott to be more persistent in damaging the sales target of a product brand. So, it is necessary to carry out further research regarding the role of religion in terms of mechanisms and further stages in influencing boycott decisions. This research aims to determine the influence of the role of religion in underlying boycott participation intentions. This research methodology uses the PLS Structural Equation Modeling (SEM) analysis tool using a sample of 385 spread evenly throughout Indonesia using a proportional sampling quota. This research aims to examine the relationship between subjective norms, attitudes and perceived control behavior in accordance with the development of boycott participation intentions. The results of this study reveal that perceived control behavior has the highest influence on intention to participate in boycotts. Keywords: Consumer Boycotts, Religious Motivation, Intention Boycotss